Frequency-Uniform Decomposition, Function Spaces , and Applications to Nonlinear Evolution Equations - Shaolei Ru; Jiecheng Chen (Journal of Function Spaces and Applications)
By combining frequency-uniform decomposition with (), we introduce a new class of function spaces (denoted by ). Moreover, we study the Cauchy problem for the generalized NLS equations and Ginzburg-Landau equations in .